Trump's Cuban Policy as a Metaphor for US Politics. Issue 4 (2nd October 2018) - Rodriguez, Raul; Targ, Harry
ABSTRACT: This paper reviews the history of US-Cuban relations. It identifies the modest but significant changes in that policy brought about by negotiations during the Barack Obama and Raul Castro Administrations. It then examines the policy reversals initiated by President Trump during his first year in office. The paper suggests that US policy toward Cuba is characteristic of US foreign policy generally.